PENINGKATAN HASIL BELAJAR IPAS MELALUI PENERAPAN MEDIA PERMAINAN ULAR TANGGA BERBASIS QR CODE - Khoirinida, Nela; Khamdun , Khamdun; Kironoratri , Lintang (Jurnal Pendidikan Dasar, 2024)
The purpose of this research is to describe  improvement IPAS learning outcomes for class V students through the application of the QR code-based snakes and ladders game. The QR code-based snakes and ladders game is a visual learning media that can support learning through collaboration with games. This research uses the classroom action research method consists of two cycles, each divided two meetings which planning, implementation, observation and reflection. Research subjects fifth grade students, with data collection techniques using interview, observation and documentation. The data analysis technique uses qualitative descriptive and quantitative descriptive statistical analysis. The results of the research showed increase IPAS learning outcomes in IPAS understanding element, cycle I, classical completeness reached 53% "Enough," criteria in cycle II it increased to 82% "Very Good." criteria. The process skills element, learning outcomes also increased from 63% "Good" criteria in cycle I to 80% "Very Good" criteria in cycle II. Based on the research results, can be concluded that TGT learning model with help of the QR code-based snakes and ladders game can improve students IPAS learning outcomes.